2022
DOI: 10.1021/acsabm.2c00618
|View full text |Cite
|
Sign up to set email alerts
|

Selective Separation of Thyroid-Hormone-Receptor-Binding Substances Using Molecularly Imprinted Polymers

Abstract: To date, an identification protocol for endocrine disruptors that bind to the thyroid hormone receptor (TR) has not been established. A method for screening and identifying TR-binding substances is highly required due to the existence of unknown TR-binding substances from the environment. Here, we conceived a chromatographic method using a molecularly imprinted polymer (MIP) to create a novel screening protocol for the endocrine disruptors. A receptor-imitating MIP was prepared using N-acetylthyroxine (AcetylT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This interaction may heterogeneously form recognition site, and thus, the column did not show sufficient imprinting effects. 40 Here, we fabricated MIP coated polymer particles that non-specific interaction does not emerge as MIP recognition sites are formed on the surface of EDMA polymer particles, the particle size of 5 μm prepared by multistep swelling and polymerization. These particles have narrow size distribution, which makes pressure resistance and separation efficiency high.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction may heterogeneously form recognition site, and thus, the column did not show sufficient imprinting effects. 40 Here, we fabricated MIP coated polymer particles that non-specific interaction does not emerge as MIP recognition sites are formed on the surface of EDMA polymer particles, the particle size of 5 μm prepared by multistep swelling and polymerization. These particles have narrow size distribution, which makes pressure resistance and separation efficiency high.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous study, the MIP using AcT4 as a template molecule and 4Vp as a functional monomer showed high adsorption selectivity toward TR biding substances. 40 After finishing polymerization, the solvents were removed by centrifugal separation. And then the particles were dispersed in the washing solvents, including 5% formic acid aq.…”
Section: Methodsmentioning
confidence: 99%